Sex education for teenagers during the COVID-19 pandemic: Report of an Extension Project (Research, Society and Development, 2022)
As a result of the COVID-19 pandemic, the number of unplanned pregnancies among adolescents, Sexually Transmitted Infections (STIs) and abuse against minors has increased. The importance of addressing issues related to sex education was then evidenced to sharpen adolescents' critical sense of such content and thus promote a broad awareness. Objective: To solve the main doubts about several fundamental themes for the individual's growth towards his adult identity, insertion in the social structure and determination of his self-esteem and affective relationships, through the development of the critical sense of adolescents regarding sex education. Methods: This is an experience report of the Project "Building sexual education in a scenario during the post-pandemic". Results: A total of 295 elementary and high school students, aged between 12 and 18 years old, were reached during 2021. Through the project, classes and conversation circles were developed, aiming to clarify doubts and instruct students. The lectures were divided into the following themes: project presentation and questioning to bring up the main doubts of young people; discussion about the questionnaire and class about consent; class on Sexually Transmitted Infections and class on Contraceptive Methods. Final Considerations: During the classes, numerous historical and cultural taboos were noted, mainly because families continue to deprive their children of emancipatory sexual education, due to the negative value attributed to sexuality, which demonstrates the fundamentality of the project, mainly for the development of sexuality, individual and collective maturation, in addition to favoring the construction and development of possible affective relationships.